A Tool Development Framework to Support Design Thinking for Software Engineering - Arslan, Ayse Kok (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2021)
This research aims to create a framework to guide the development of design thinking support tools - that is, tools that enable people to express themselves creatively and develop as creative thinkers. The main goal is to develop advanced software and social networking sites that empower users to not only be productive, but also have new technologies. Potential users of these interfaces include software with other engineers, various scientists, product and image designers, builders, teachers, students and many more. Improved communication methods can enable effective psychological search, improved interaction between groups, and faster recovery processes. These advanced combinations should also provide strong support for hypothesis formation, rapid testing of alternatives, improved visual perception, and better distribution of results.